EQUIPMENT AND OTHER CONDITIONS IN PRIMARY SCHOOLS FOR THE REALIZATION OF PHYSICAL EDUCATION CLASSES TEACHER'S CONTRIBUTION TO THE REALIZATION OF CLASSES - Dragan Martinović; Dragan Branković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Candidates eligible for the enrollment at the Teacher training Faculty have fi lled in a questionaire and expressed their views on four groups of issues related to the physical education classes in primary schools. The fi rst group of questions related to the material and technical conditions of the school, the second group to the utilisation of the existing conditions by the teachers and also number of sports and recreational activities in schools. The third and the fourth groups of question referred to effect of the physical education classes on the development of individual interests in the contents of the physical education classes and the contribution of the teachers in realization of classes.